Unravelling Passive Social Media Use Through Screenomes - Yee, Andrew Z. H.; Krause, Hannes-Vincent; Meier, Adrian; Ng, Li Yin; Loy, Guan Peng (74th Annual ICA Conference, 2024)
The active-passive framework to social media use and well-being promised nuanced insights, yet effects of passive use have been mixed. One reason could be the enormous heterogeneity of the ‘passive use’ concept, which encompasses various social media features, actions, and contents. This study applies the conceptual lenses of the hierarchical CMC taxonomy and social media content genres to unpack and explore this heterogeneity of passive social media use. We use a random sample of smartphone screenshots (‘screenomics’) drawn from 703,827 sequential screenshots collected from 20 participants over a two-week period to content analyze 10,000 screenshots. Results reveal substantial heterogeneity and patterns within passive use across four analytical levels: branded application, feature, modality, and content topics/genres. As the effects of social media on well-being may often be caused by content or design features, our study provides insights into how passive use can be broken down into more meaningful units of analysi
Keywords: social media; active-passive model; screenomics; well-being; content analysis